2017
DOI: 10.1097/qai.0000000000001402
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Use and HIV-Related Behaviors of Black and Latina Transgender Women in 3 US Metropolitan Areas: Results From the Transgender HIV Behavioral Survey

Abstract: Purpose HIV prevalence estimates among transgender women in the United States are high, particularly among racial/ethnic minorities. Despite increased HIV risk and evidence of racial disparities in HIV prevalence among transgender women, few data are available to inform HIV prevention efforts. Methods A transgender HIV-related behavioral survey conducted in 2009 in 3 US metropolitan areas (Chicago, Houston, and Los Angeles County), used respondent-driven sampling to recruit 227 black (n = 139) and Latina (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Lack of use of hormones was also associated with a severalfold increased odds of HIV infection. Under half of transgender women in our survey had ever taken hormones and fewer than one in five had ever had gender-affirming surgery, figures that are quite low compared with those of other countries [3, 9,26]. At least one study in China documented a large unmet need and desire for gender transition care, including 90% demand for hormones and 50% demand for gender-affirming surgery [27].…”
Section: Discussionmentioning
confidence: 83%
“…Lack of use of hormones was also associated with a severalfold increased odds of HIV infection. Under half of transgender women in our survey had ever taken hormones and fewer than one in five had ever had gender-affirming surgery, figures that are quite low compared with those of other countries [3, 9,26]. At least one study in China documented a large unmet need and desire for gender transition care, including 90% demand for hormones and 50% demand for gender-affirming surgery [27].…”
Section: Discussionmentioning
confidence: 83%
“…These sexual behaviors may contribute to the high prevalence of HIV and STDs among transgender adolescents. Additionally, behaviors developed during adolescence may contribute to the high prevalence of HIV and STDs in young adult transgender populations . These findings highlight the need for effective interventions to help promote protective behaviors such as condom use among transgender adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Racial and ethnic minority transgender adults may disproportionately be affected. For example, one study found as many as 29% of Black and Latina transgender women self‐reported being HIV positive in 3 US metropolitan areas . Less is known about HIV prevalence among gender non‐binary adults; however, one study suggests they may have an HIV prevalence equal to or greater than those who identify as transgender men or transgender women .…”
mentioning
confidence: 99%
“…In California, transgender female clients of publicly-funded counseling and testing sites have higher rates of HIV diagnosis (6%) than all other risk categories, including MSM (4%) and partners of people living with HIV (5%), and African American transgender women have a particularly high rate of HIV diagnosis (29%) (10). Estimates from other urban centers in the US similarly suggest that HIV prevalence rates among transgender women are among the highest of all key populations, especially for transgender women of color, and African American transgender women are most severely impacted (8,11,12).…”
Section: Introductionmentioning
confidence: 99%